Human-Computer Interaction in Agricultural User Interfaces - Ibrahim, Umar; Danmaigoro, Aliyu (International Journal of Applied and Scientific Research, 2024)
This study explores the intersection of Human-Computer Interaction (HCI) and agricultural user interfaces, aiming to enhance the efficiency and user experience within the agricultural domain. A thorough literature review identifies current trends, challenges, and gaps in HCI research specific to agricultural interfaces. The research objectives encompass the proposal of HCI design principles tailored to the unique characteristics of the agricultural environment. Methodologically, the study employs user surveys, interviews, and usability testing to gather insights into user preferences and challenges. The paper presents case studies highlighting successful implementations of HCI principles in agricultural settings, providing tangible examples of improved user engagement and task performance. Challenges and limitations in HCI adoption in agriculture are discussed, along with user feedback and evaluations shaping interface design. The implications of the research extend to HCI practitioners, agricultural technology developers, and policymakers, offering practical insights for future developments. This paper contributes valuable knowledge to the evolving field of HCI in agricultural contexts, emphasizing the importance of user-centered design.